2020
DOI: 10.17582/journal.pjz/20190330090327
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Bionomics of Dusky Cotton Bug (Oxycarenus laetus) (Lygaeidae: Hemiptera) on Three Different Hosts

Abstract: Authors' Contribution MS performed the experiments. SMZ supervised the work. SMTAS coordinated the experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Dusky cotton bugs were also observed causing injury, not only to cotton seeds but also to its stems and leaves as well. These observations are in agreement with the findings of Sarmad et al (2020) . The cotton plant is a preferred choice of this pest ( Sarmad et al, 2020 ) and it attacks about 40 different host plants ( Schaefer and Panizzi, 2000 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Dusky cotton bugs were also observed causing injury, not only to cotton seeds but also to its stems and leaves as well. These observations are in agreement with the findings of Sarmad et al (2020) . The cotton plant is a preferred choice of this pest ( Sarmad et al, 2020 ) and it attacks about 40 different host plants ( Schaefer and Panizzi, 2000 ).…”
Section: Discussionsupporting
confidence: 93%
“…The cotton plant is a preferred choice of this pest ( Sarmad et al, 2020 ) and it attacks about 40 different host plants ( Schaefer and Panizzi, 2000 ). It causes economic loss in almost all cotton growing areas of the world ( Sarmad et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…hirsutum was most suitable followed by A . indicum and A. esculentus 72,73 . Therefore, it is concluded that season management of this pest is mainly done in G. hirsutum 74 and on A. esculentus to a comparatively lesser extent 3 .…”
Section: Discussionmentioning
confidence: 97%